2018
DOI: 10.1097/htr.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Community-Based Healthy Lifestyle Program on Individuals With Traumatic Brain Injury

Abstract: Participants demonstrated high adherence with the program, suggesting that individuals with TBI are able to successfully engage in the program and achieve significant weight loss and changes in key physiologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Registered dietitians (6%) 19,35,89,107,112 and physical therapists (1%) 23 were also among those health care providers who delivered interventions. Exercise/health coaches and counselors (22%), 21,22,27,30,31,37,63,67,72,83-85,87,95-97,105 research staff (18%), 18,24,33,64,69,75,78,82,88,89,91,92,98,114 trained health practitioners (15%) 20,38,71,73,74,79,87,99,109-112 (eg, medical assistants), and trained/certified health educators (13%) 17,25,28,29,74,98,105,107,108,112 (eg, diabetes educators) made up almost the same proportion of interventionists as physicians and nurses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Registered dietitians (6%) 19,35,89,107,112 and physical therapists (1%) 23 were also among those health care providers who delivered interventions. Exercise/health coaches and counselors (22%), 21,22,27,30,31,37,63,67,72,83-85,87,95-97,105 research staff (18%), 18,24,33,64,69,75,78,82,88,89,91,92,98,114 trained health practitioners (15%) 20,38,71,73,74,79,87,99,109-112 (eg, medical assistants), and trained/certified health educators (13%) 17,25,28,29,74,98,105,107,108,112 (eg, diabetes educators) made up almost the same proportion of interventionists as physicians and nurses.…”
Section: Resultsmentioning
confidence: 99%
“…26,108 Seven studies (9%) used other, more unique measures to assess physical function, including timed and distance walking tests 27,30,33,74,86,109 and balance scales. 23 In terms of reported findings, 57 studies (73%) [17][18][19]21,22,24,26,27,[32][33][34][35][36][37][38][39][40]62,63,[65][66][67][68][69][70][71]73,74,76,80,82,83,[85][86][87][88][89][90][91][92][94][95]…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…Analysis of pilot data determined a required sample size of 66 participants (33 per group) to detect a 5% reduction in weight (GLB-TBI program goal), with a power of 0.8 and assuming a 15% attrition rate (observed during our pilot study). These estimates are based upon the GLB-TBI weight-loss data which included weight at baseline (212 ± 35lbs) and weight-loss after 12 months (10.2 ± 13lbs) [ 3 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Group Lifestyle Balance (GLB) intervention is a 12-month, evidence-based physical activity and healthy eating program that has been used extensively with the general population [ [15] , [16] , [17] ], but not with people with TBI. Researchers modified the program [ 18 ] to meet the needs of people with a TBI (GLB-TBI) and pilot results with 18 individuals with TBI demonstrated that participation resulted in 5% weight-loss (10.2 ± 13lbs) over 12-months [ 19 ]. To generate strong evidence of the GLB-TBI efficacy for promoting weight loss, this protocol paper describes a randomized controlled trial of the GLB-TBI Intervention compared to an attention-matched Support Group-based Educational Intervention.…”
Section: Introductionmentioning
confidence: 99%
“…; p = .0048), and total cholesterol (−24 mg/dl; p = .0247). No significant changes were observed in self-reported health (Driver et al, 2018). Findings suggest that participants with TBI engaged in the program and that engagement may support improved health, although a more rigorous study design is required (e.g., randomized controlled trial, larger sample).…”
Section: Introductionmentioning
confidence: 90%